Scheduling of Irrigation and Leaching Requirements (Journal of Engineering, 2015)
Iraq depends mainly on Tigris and Euphrates Rivers to provide high percentage of agricultural water use for thousands years. At last years, Iraq is suffering from shortage in water resources due to global climate changes and unfair water politics of the neighboring countries, which affected the future of agriculture plans for irrigation, added to that the lack of developed systems of water management in the irrigation projects and improper allocation of irrigation water, which reduces water use efficiency and lead to losing irrigation water and decreasing in agricultural yield. This study aims at studying the usability of irrigation and leaching scheduling within the irrigating projects and putting a complete annual or seasonal irrigation program as a solution for the scarcity of irrigation water, the increase of irrigation efficiency, lessening the salinity in the projects and preparing an integral irrigation calendar through field measurements of soil physical properties and chemical for project selected and compared to the results of the irrigation scheduling and leaching with what is proposed by the designers. The process is accomplished by using a computer program which was designed by Water Resources Department at the University of Baghdad, with some modification to generalize it and made it applicable to various climatic zone and different soil types. Study area represented by large project located at the Tigris River, and this project was (Al-Amara) irrigation project. Sufficient samples of project's soil were collected so as to identify soil physical and chemical properties and the salinity of soil and water as well as identifying the agrarian cycles virtually applied to this project. Finally, a comparison was conducted between the calculated water quantities and the suggested ones by the designers. The research results showed that using this kind of scheduling (previously prepared irrigation and leaching scheduling) with its properties which made it applicable requires an intense care when using the plant distribution pattern, the agrarian cycle, its agrarian areas and agricultural intensity within all climatic regions. Also, it was found that this program was an instrumental tool for providing water if the plant distribution pattern was well-selected.